Effect of Different Methods for the Overhang Amalgam Restorations Removal on Periodontal Health Status - Dana M. Yawer Aldalawi; Dara H. Saeed; Sangar H. Ali (Polytechnic)
Overhanging tooth restorations due to environmental change of the balance between beneficial bacteria and periodontopathogens lead to periodontal breakdown. This study aim was to evaluate the periodontal status after using different techniques for amalgam overhang removal. The proximal restorations were examined clinically and then radiographically by taking bitewing radiograph. From a total of 1200 patients examined in College of Dentistry, Hawler Medical University and (Khanzad) Specialized Centre for Dentistry for presence of proximal amalgam restoration, for this interventional and prospective study, 45 patients with amalgam overhang were divided into three groups each 15 patients according to size and position of amalgam overhang each had one type of the following treatment (Refilling, Diamond Bur, EVA system) and 15 patients without amalgam overhang (control group) selected completed the trial. Clinical periodontal parameters were measured in teeth with amalgam overhang at baseline, 2 week, 1 and 3 months after removal of amalgam overhang. The results showed that the periodontal parameters showed a gradual decrease in all groups throughout the follow-up visits (except calculus index) and became a statistically significant in the 3 months follow-up following treatment (P < 0.001), with more reduction found in refilling group followed by EVA system then diamond bur group. In conclusion that it is better to replace the restoration rather than to use the other methods of treatment according to periodontal health which recorded by periodontal parameters.